Statistika Pendidikan sebagai Instrumen Pengambilan Keputusan Berbasis Data dalam Manajemen Pendidikan Islam di Era Artificial Intelligence - Ahmad Arpandi (Kartika: Jurnal Studi Keislaman, 2026)
This conceptual research aims to reconstruct the strategic role of educational statistics as a primary instrument for Data-Driven Decision Making (DDDM) within Islamic Educational Management (IEM) amidst the disruption of the Artificial Intelligence (AI) era. Employing a theoretical conceptual study and an in-depth content analysis approach, this paper systematically integrates quantitative analytical functions, AI-driven predictive analytics, and Islamic leadership ethics. The findings affirm that educational statistics serves far beyond administrative duties; it acts as the core foundation for scientific reasoning and methodological quality control that validates AI algorithmic outputs, preventing reliance on opaque black-box systems. The synergy between statistical precision and AI processing velocity generates exceptionally accurate prescriptive analytical capabilities for institutional management. Furthermore, this study proposes a comprehensive four-stage strategic model comprising Data Harvesting & Governance, Statistical & AI Processing, Ethical & Values Screening, and Actionable Policy & Evaluation. By filtering insights through core Islamic values such as syura, 'adl, amanah, and maslahah the framework ensures that data-driven recommendations remain strictly under human moral oversight. This conceptual reconstruction offers a transformative paradigm for modern, objective, and ethically sound Islamic educational governance.